2021
DOI: 10.1186/s12887-021-02931-6
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal prognostic factors for isolated right congenital diaphragmatic hernia: a single center’s experience

Abstract: Background Right-sided congenital diaphragmatic hernia (RCDH) is relatively rare compared with left-sided congenital diaphragmatic hernia (LCDH). Clinical data of RCDH, especially with respect to antenatal prediction of neonatal outcome, are lacking. The aim of this study was to report the treatment outcomes of patients with antenatally diagnosed RCDH and to evaluate the predictability of observed-to-expected lung area-to-head circumference ratio (O/E LHR) for perinatal outcomes, focused on mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A large diaphragmatic defect and massive herniation of abdominal viscera compresses the fetal lung, affecting its development. Additional prognostic factors in CDH are fetal development and lung volume [ 10 ], especially in case of liver herniation [ 20 ]. Liver herniation into the right chest cavity was observed in both our cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large diaphragmatic defect and massive herniation of abdominal viscera compresses the fetal lung, affecting its development. Additional prognostic factors in CDH are fetal development and lung volume [ 10 ], especially in case of liver herniation [ 20 ]. Liver herniation into the right chest cavity was observed in both our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent nationwide cohort study performed in France also reported the survival rate was 57 % for rCDH and 77 % for lCDH with statistical difference ( P < .01) [ 6 ]. However, late-onset rCDH has also been reported [ 9 ], and some recent studies found no significant difference in mortality or morbidity if lung volume was sufficient and appropriate treatment was performed [ 4 , 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the upper airway parameters, influenced by biomechanics and lung liquid, might reflect true lung function. Some scholars once believed that the LHR only has prognostic value in left-sided CDH [ 32 ], however, recent research indicates that LHR can also be used for right diaphragmatic hernia [ 37 ]. Meanwhile, the upper airway parameters may be associated with overall lung development, thereby possessing prognostic value for potentially all types of CDH.…”
Section: Discussionmentioning
confidence: 99%
“…RSCDH are linked to a higher mortality rate, often attributed to larger defect sizes. Research also indicates that the defect's size, rather than its lateralisation, plays a more pivotal role in determining the prognosis [5][6][7] (Table 1).…”
Section: Discussionmentioning
confidence: 99%